2008
DOI: 10.1103/physreve.77.046119
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of community structure in networks

Abstract: The discovery of community structure is a common challenge in the analysis of network data. Many methods have been proposed for finding community structure, but few have been proposed for determining whether the structure found is statistically significant or whether, conversely, it could have arisen purely as a result of chance. In this paper we show that the significance of community structure can be effectively quantified by measuring its robustness to small perturbations in network structure. We propose a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
287
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(291 citation statements)
references
References 42 publications
2
287
0
2
Order By: Relevance
“…On the other hand, Guimerà, Sales-Pardo, and Amaral [85] and Fortunato and Barthélemy [73] showed that random graphs have high-modularity subsets and that there exists a size scale below which communities cannot be identified. In part as a response to this, some recent work has had a more statistical flavor [86,140,144,94,133]. In light of our results, this work seems promising, both due to potential "overfitting" issues arising from the extreme sparsity of the networks, and also due to the empirically-promising regularization properties exhibited by local spectral methods.…”
Section: Relationship With Community Identification Methodsmentioning
confidence: 78%
See 2 more Smart Citations
“…On the other hand, Guimerà, Sales-Pardo, and Amaral [85] and Fortunato and Barthélemy [73] showed that random graphs have high-modularity subsets and that there exists a size scale below which communities cannot be identified. In part as a response to this, some recent work has had a more statistical flavor [86,140,144,94,133]. In light of our results, this work seems promising, both due to potential "overfitting" issues arising from the extreme sparsity of the networks, and also due to the empirically-promising regularization properties exhibited by local spectral methods.…”
Section: Relationship With Community Identification Methodsmentioning
confidence: 78%
“…For these networks, the interpretation is similar to that for the low-dimensional networks: the downward slope indicates that as potential communities get larger and larger, there are relatively more intra-edges than inter-edges; and empirically we observe that local minima in the NCP plot correspond to sets of nodes that are plausible communities. Consider, e.g., Zachary's karate club [160] network (ZacharyKarate), an extensivelyanalyzed social network [128,131,94]. The network has 34 nodes, each of which represents a member of There are two local minima in the plot: the first dip at k = 5 corresponds to the Cut A, and the second dip at k = 17 corresponds to Cut B.…”
Section: Observation 1 If the Network Under Consideration Correspondsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the analysis of network data, many methods have been proposed for finding communities, but few have been proposed for determining whether the distribution breakdown found is statistically significant or a result of chance. With the method used here, the significance of community structure can be effectively quantified by measuring its robustness to small perturbations in network structure (Karrer et al, 2008), using the modularity Q. In principle, the maximum value of the modularity is Q max 5 1 and such a network could be considered as highly modular.…”
Section: Discussionmentioning
confidence: 99%
“…Through the use of surrogate chemical randomisations 37 , we have shown that Markov Stability is able to detect chemical groups, biochemical units, as well as structural features such as helical turns. At long Markov times, we look for significant partitions with the defining feature of being robust to perturbations 42 . We use two measures to quantify this robustness:…”
Section: Construction Of the Atomistic Networkmentioning
confidence: 99%